The benefits and harms of deprescribing. Issue 7 (6th October 2014) - Reeve, Emily; Shakib, Sepehr; Hendrix, Ivanka; Roberts, Michael S; Wiese, Michael D
Summary: Deprescribing is the process of trial withdrawal of inappropriate medications. Currently, the strongest evidence for benefit of deprescribing is from cohort and observational studies of withdrawal of specific medication classes that have shown better patient outcomes, mainly through resolution of adverse drug reactions. Additional potential benefits of deprescribing include reduced financial costs and improved adherence with other medications. The harms of ceasing medication use include adverse drug withdrawal reactions, pharmacokinetic and pharmacodynamic changes and return of the medical condition. These can be minimised with proper planning (ie, tapering), monitoring after withdrawal, and reinitiation of the medication if the condition returns. More evidence is needed regarding negative, non‐reversible effects of ceasing use of certain classes of medication, such as acetylcholinesterase inhibitors. Cessation of use has not been studied for many medication classes, and large‐scale randomised controlled trials of systematic deprescribing are required before the true benefits and harms can be known.